PROFIL PENANGGULANGAN KEMISKINAN DAERAH KABUPATEN SUMENEP - Jakfar Sadik (MediaTrend, 2014)
National Development that was held simultaneously with the spirit regionalautonomy refer to the three strategy: Pro-Growth, Pro Job, and Pro-Poor Budget whichare all at the center of the goals that the make-up of prosperity to eradicate povertyreduction through. Sumenep Regency community people out of Poverty is the majoritymultidimensional, education primary school students, the access appropriate sanitationand clean water still enjoyed a few people, the people who have not enjoyed the flow ofelectricity PLN is almost 40% especially in the region the islands, sea transport andrural areas also adopted by less than that inhibit mobility and work in economicactivities in the region. Poverty alleviation programs Sumenep Regency region isdivided into 3 clusters including: the program social assistance based integratedpoverty alleviation programs, family-based pemberdaaan poverty alleviation programs,community-based micro and small business development. From the three clusters havebeen integrated between the national, provincial and district levels. Many achievementalso have been achieved by Poverty alleviation programs in Sumenep Regency area,including; The Education indicators population, The Health community indicators, TheBasic Infrastructure, and The indicator for Food.